Pengaruh Tactical Games Model Terhadap Hasil Belajar Aspek Psikomotor pada Pembelajaran Bolavoli Siswa SMPN 1 Kalijati - Gustiana Pramudia Wardani; Ismaya, Bambang; Dermawan, Dikdik Fauzi (Jurnal Porkes, 2024)
This study aims to examine the effect of the tactical games model (TGM) on learning outcomes of psychomotor aspects in bolavoli learning. This research method uses quantitative. With this research using pretest posttest control group design. The subjects of learning research are students of SMPN 1 Kalijati. This sample was selected using random sampling technique, based on this explanation, two classes were obtained, for the experimental group using class A which amounted to 35 people and for the control group using class B which amounted to 35 people this research was conducted 10 times. This research instrument is the game performance assessment instrument. The results of the pretest and posttest data analysis obtained from the experimental group's posttest values from each test instrument have the results of the paired sample T-test test value with the “test statistic” output with a value of -t count < -t table (-8.313 < -1.690) and the significance value obtained is 0.000 which is < 0.05, so there is a significant influence between the Tactical Games Model on the learning outcomes of the psychomotor aspects of the pretest and posttest data.